2022
DOI: 10.3390/ijms232415543
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli as a New Platform for the Fast Production of Vault-like Nanoparticles: An Optimized Protocol

Abstract: Vaults are protein nanoparticles that are found in almost all eukaryotic cells but are absent in prokaryotic ones. Due to their properties (nanometric size, biodegradability, biocompatibility, and lack of immunogenicity), vaults show enormous potential as a bio-inspired, self-assembled drug-delivery system (DDS). Vault architecture is directed by self-assembly of the “major vault protein” (MVP), the main component of this nanoparticle. Recombinant expression (in different eukaryotic systems) of the MVP resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Thus, by fusing it at the C-terminus of cargo proteins or by otherwise binding it to diverse compounds, they can be taken up and stably incorporated into the nano-assembly. Interestingly, a sheer co-incubation of the latter with INT-tagged proteins results in spontaneous association of the two molecular partners [ 40 , 41 , 42 ], an occurrence also favored by the dynamic nature of the vault assembly [ 43 , 44 ]. Strikingly, a recent report describes internalization by the vault NP of whole, INT-fused, adeno-associated virus particles, which further highlights its remarkable potential as a carrier of diverse cargo molecules [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by fusing it at the C-terminus of cargo proteins or by otherwise binding it to diverse compounds, they can be taken up and stably incorporated into the nano-assembly. Interestingly, a sheer co-incubation of the latter with INT-tagged proteins results in spontaneous association of the two molecular partners [ 40 , 41 , 42 ], an occurrence also favored by the dynamic nature of the vault assembly [ 43 , 44 ]. Strikingly, a recent report describes internalization by the vault NP of whole, INT-fused, adeno-associated virus particles, which further highlights its remarkable potential as a carrier of diverse cargo molecules [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the baculovirus–insect cell system is complex and time consuming [ 9 ], whereas the human-cell-based procedure is definitely simpler [ 19 ], but both of them hardly lend themselves to a significant scale up. Conversely, the recently developed E. coli -based protocol actually allows a substantial simplification of the process, but only enables the production of a vault variant consisting of His-tagged MVP subunits [ 20 ]. The present contribution reports a novel protocol that overcomes these limitations by combining the use of an engineered K. phaffii strain as the expression system of an authentic vault [ 21 ] with a purification procedure that represents a modification of a previously reported one [ 22 ], now essentially consisting of the RNase treatment of yeast-cell-free extracts and a subsequent SEC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a more simplified procedure was developed by expressing a His-tagged vault variant in human embryonic kidney cells, which made it possible to affinity-purify the nanocomplex [ 19 ]. The same research group subsequently reported an Escherichia coli -based protocol, which unquestionably represents a substantial improvement in terms of process simplification [ 20 ]. Yet, it might suffer from obvious restraints related to the production of a non-natural, His-tagged variant, mainly in view of its employment as a nanovector to be administered to cells or whole organisms.…”
Section: Introductionmentioning
confidence: 99%